‘Taking the politics out of broccoli’: debating (de)meatification in UK national and regional newspaper coverage of the Meat Free Mondays campaign - Morris, Carol (Wiley, 2017)
This paper addresses UK society’s relationship with meat and specifically explores the extent to which a process of ‘de-meatification’ is underway in this context and one of the mechanisms involved. It does so through analysis of reporting of the Meat Free Mondays (MFM) campaign in the national and regional British print news media. MFM offers a convenient yet powerful vehicle for trying to understand shifting meanings of meat not least because it directly challenges, and generates debate about the dominant – meat based – diet. The paper concludes by arguing that a shift is taking place in the status of meat within UK society with the print news media acting as a mechanism that is working in support of de-meatification. However, these conclusions are qualified in a number of important ways, including the anthropocentrism of the (de)meatification debate, its geographical variability and its weakly politicised character.